Ocean Floor Observation and Bathymetry System (OFOBS) seafloor images and videos of the Fram Strait collected during RV POLARSTERN cruise PS143/1 - Boehringer, Lilian; Purser, Autun; Bergmann, Melanie; Khan, Tasnuva Ming; Schimpf, Karsten; Krämmer, Christopher (PANGAEA, 2025)
During the RV POLARSTERN cruise PS143/1 (2024-06-07 to 2024-07-09) to the long-term ecological research station HAUSGARTEN observatory in the Fram Strait the Ocean Floor Observation and Bathymetry System (OFOBS) was used to collect still images and video footage from various locations surveyed during the expedition. The OFOBS consisted of a towed underwater camera system equipped with a high-resolution photo-camera (iSiTEC, CANON EOS 5D Mark III) and a high-definition video-camera (iSiTEC, Sony FCB-H11) as well as an integrated sidescan sonar system. The cameras were mounted on a steel frame (140 L x 92 W x 135 H cm), together with two strobe lights (iSiTEC UW-Blitz 250, TTL driven), three laser pointers spaced with a distance of 50 cm used to estimate the size of seafloor structures, four LED lights, and a USBL positioning system (Posidonia) to track the position of the OFOBS during deployments, with additional positioning information provided by the integrated INS and DVL systems. An automatic seafloor image was taken every 20 seconds to obtain 'TIMER' stills distributed at regular distances along each of the survey profiles. Additional 'MANUAL' photos were triggered individually when interesting objects appeared in the live feed. In total, 10 OFOBS deployments were carried out. If no positions for the OFOBS were available, the ships position was used instead. Metadata in the form of iFDOs are available for each deployment containing a detailed description of the image and video data collection and curation process.
Keywords: Benthos; Deep-sea ecology; Fram Strait; HAUSGARTEN Long Term Observatory; iFDO; Seafloor images